Respostas

2013-11-19T20:17:33-02:00
A)
Δ = b² -4ac
Δ = (-49)² -4 *3 * 0
Δ = 2401 0
Δ = 2401
x' = (-b + √∆)/ 2a
(-(-49) + 49)/2 * 3
(49 + 49)/6
98/6= 16,3333333333333
x'' = (-b - √∆)/ 2a
(-(-49) - 49)/2 * 3
(49 - 49)/6
0/6= 0


b)
Δ = b² -4ac
Δ = (-50)² -4 *(-9) * 0
Δ = 2500 0
Δ = 2500
x' = (-b + √∆)/ 2a
(-(-50) + 50)/2 * (-9)
(50 + 50)/-18
100/-18= -5,55555555555556
x'' = (-b - √∆)/ 2a
(-(-50) - 50)/2 * (-9)
(50 - 50)/-18
0/-18=0

c)
Δ = b² -4ac
Δ = (-10)² -4 *7 * 0
Δ = 100 0
Δ = 100
x' = (-b + √∆)/ 2a
(-(-10) + 10)/2 * 7
(10 + 10)/14
20/14= 1,42857142857143
x'' = (-b - √∆)/ 2a
(-(-10) - 10)/2 * 7
(10 - 10)/14
0/14= 0
1 5 1
2013-11-19T20:25:57-02:00
a)3x²-49=0
3x
²=49
x²=49/3
x= \sqrt{49/3}

b) x= \sqrt{-50/9}

c)x= \sqrt{10/7}

Poderia, talvez, usar Bhaskara. Mas ficaria mt grande.

1 5 1